Present Scenario of Wood and Agro-Based Micro, Small and Medium Enterprises in Eastern Uttar Pradesh and Prospective for its Future Development - Khan, Faraz Ahmad; Tomar, Anita; Mishra, Charlie (Indian Forester, 2021)
Eastern Uttar Pradesh comprising of 27 districts is less industrialised and underdeveloped due to fewer number of industries and established MSMEs in the region. This case study illustrates the huge potential for development of new MSME sector like furniture industry, paper and paper product industry and fruit processing units in the region. For present case study the eastern Uttar Pradesh has been divided into 3 regions viz. Tarai region, Ganga-Ghaghra doab region and Vindhyan upland. The Ganga-Ghaghra doab region has maximum wood and agro-based micro, small and medium enterprises i.e. 21358 units followed by Tarai region and Vindhya region having 11548 units and 2287 units respectively. Average number of wood based micro and small enterprises and artisan units is minimum for Vindhyan region i.e. 726.33 and maximum for Ganga-Ghaghra Doab i.e.1642.92. The share of eastern UP in wood based industries is only 6.59%. The study reflects that MSMEs can be boon and a hope for economy of the region in near future and establishment of timber/furniture industry in Gorakhpur and paper manufacturing unit in Sonebhadra district will result in overall development of the state.